A review on the recent research progress in the compound parabolic concentrator (CPC) for solar energy applications - Tian, Meng; Su, Yuehong; Zheng, Hongfei; Pei, Gang; Li, Guiqiang; Riffat, Saffa (Elsevier, 2018)
Compound parabolic concentrator (CPC) has been gaining ever-increasing attention from academic researchers and industrial developers owing to its stationary feature for solar energy collection with a higher efficiency. As a low concentration concentrator with a larger acceptance angle and without a tracking requirement, it is an attractive solution to improve the system performance and reduce the cost of photovoltaic (PV) system, solar thermal system, daylighting and lighting systems, etc. This study will present a comprehensive and up-to-date review of its design principles for miscellaneous configurations, applications, performance predictions and technological advances. Numerous technically focused studies since 2000 will be introduced and summarized. Finally, the outlook focusing on CPC designs and improvements will be proposed.